2019
DOI: 10.1021/acs.inorgchem.9b02737
|View full text |Cite
|
Sign up to set email alerts
|

Lewis versus Brønsted Acid Activation of a Mn(IV) Catalyst for Alkene Oxidation

Abstract: Lewis acid (LA) activation by coordination to metal oxido species has emerged as a new strategy in catalytic oxidations. Despite the many reports of enhancement of performance in oxidation catalysis, direct evidence for LA-catalyst interactions under catalytically relevant conditions is lacking. Here, we show, using the oxidation of alkenes with H2O2 and the catalyst [Mn2(μ-O)3(tmtacn)2](PF6)2 (1), that Lewis acids commonly used to enhance catalytic activity, e.g., Sc(OTf)3, in fact undergo hydrolysis with adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…These results contrast the recent report that adding 1 equiv of either Sc­(OTf) 3 or HClO 4 to [Fe III (β-BPMCN)­(OOH)] 2+ (where β-BPMCN = cis -β-bis­(pyridyl-2-methyl)- cis -1,2-diaminocyclohexane) generates an oxidant capable of hydroxylating cyclohexane within seconds at −40 °C . Browne and co-workers have also provided strong evidence that the Sc­(OTf) 3 -enhanced olefin epoxidation by the combination of [Mn IV 2 (μ-O) 3 (tmtacn) 2 ] 2+ (where tmtacn = 1,4,7-trimethyl-1,4,7-triazacyclononane) and H 2 O 2 results from Brønsted acid formation upon hydrolysis of Sc­(OTf) 3 by water present in the reaction mixture . In contrast to these two examples, our system is unique in that the added acid (Brønsted or Lewis) has a choice between attacking the oxo bridge versus the peroxide bridge in a diiron model framework, resulting in significantly different outcomes from Brønsted and Lewis acids.…”
Section: Summary and Perspectivescontrasting
confidence: 71%
See 1 more Smart Citation
“…These results contrast the recent report that adding 1 equiv of either Sc­(OTf) 3 or HClO 4 to [Fe III (β-BPMCN)­(OOH)] 2+ (where β-BPMCN = cis -β-bis­(pyridyl-2-methyl)- cis -1,2-diaminocyclohexane) generates an oxidant capable of hydroxylating cyclohexane within seconds at −40 °C . Browne and co-workers have also provided strong evidence that the Sc­(OTf) 3 -enhanced olefin epoxidation by the combination of [Mn IV 2 (μ-O) 3 (tmtacn) 2 ] 2+ (where tmtacn = 1,4,7-trimethyl-1,4,7-triazacyclononane) and H 2 O 2 results from Brønsted acid formation upon hydrolysis of Sc­(OTf) 3 by water present in the reaction mixture . In contrast to these two examples, our system is unique in that the added acid (Brønsted or Lewis) has a choice between attacking the oxo bridge versus the peroxide bridge in a diiron model framework, resulting in significantly different outcomes from Brønsted and Lewis acids.…”
Section: Summary and Perspectivescontrasting
confidence: 71%
“…70 Browne and co-workers have also provided strong evidence that the Sc(OTf) 3 -enhanced olefin epoxidation by the combination of [Mn IV 2 (μ-O) 3 (tmtacn) 2 ] 2+ (where tmtacn = 1,4,7-trimethyl-1,4,7-triazacyclononane) and H 2 O 2 results from Brønsted acid formation upon hydrolysis of Sc(OTf) 3 by water present in the reaction mixture. 71 In contrast to these two examples, our system is unique in that the added acid (Brønsted or Lewis) has a choice between attacking the oxo bridge versus the peroxide bridge in a diiron model framework, resulting in significantly different outcomes from Brønsted and Lewis acids. Most importantly, our investigations into the conversion of 2 to 3 establish that both O atoms of one O 2 end up becoming incorporated into the high-valent diiron For L = 6-Me 3 TPA and BnBQA (black), an Fe III −O−Fe IV species is formed upon protonation of the peroxo intermediate.…”
Section: ■ Summary and Perspectivesmentioning
confidence: 99%
“…The reaction was initiated by the protonation of 1 a by TfOH generated in situ via the hydrolysis of M(OTf) n . [13] Next, nucleophilic displacement at the C4 position by trace amounts of water from the solvent produced the hydrolyzed intermediate D. Subsequent C3-site addition and aromatization course delivered compound 7 a.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that Sc(OTf) 3 underwent rapid hydrolysis by residual water in MeCN (ca. 0.5–3 mM H 2 O) to generate HOTf under the conditions used for catalytic oxidations with H 2 O 2 and a Mn(II) complex [Mn 2 ( μ ‐O) 3 (tmtacn) 2 ](PF 6 ) 2 (tmtacn= N , N ′, N ′′‐trimethyl‐1,4,7‐triazacyclononane) [23] . It should be noted that [(Bn‐TPEN)Mn IV (O)] 2+ −(Sc(OTf) 3 ) 2 ( λ max =690 nm) is clearly different from a HOTf‐bound complex, [(Bn‐TPEN)Mn IV (O)] 2+ −(HOTf) 2 ( λ max =560 nm) in TFE/MeCN ( v/v =1 : 1) [24] .…”
Section: Resultsmentioning
confidence: 99%
“…. [23] It should be noted that [24] In addition, a CSI-MS spectrum of [(Bn-TPEN)Mn IV (O)] 2 + À Sc(NO 3 ) 3 ( Figure 3) clearly indicates the binding of Sc(NO 3 ) 3 rather than HNO 3 .…”
Section: Binding Of Scandium Nitrate To An Mn(iv)-oxo Complexmentioning
confidence: 98%